The Use of Blockchain Technology to Enhance Security and Transparency in Educational Certification - AR, Muslim (Universitas Nurul Jadid Probolinggo, Indonesia, 2022)
This research explores the application of blockchain technology in educational certification to enhance security and transparency. The primary focus of the study is to understand how blockchain technology can strengthen the integrity of certification data and facilitate open auditing. Employing a qualitative case study approach, data was collected through in-depth interviews and observations at an elementary school that has implemented blockchain in its certification process. The findings reveal that blockchain implementation enables immutable recording of certificates and transparent transaction verification, significantly reducing the risk of data manipulation and forgery. Additionally, the blockchain system provides publicly accessible records for authorities, speeding up the audit process and increasing public trust in the certification system. These findings indicate that blockchain technology not only improves the security and integrity of educational certification but also enhances the transparency of the certification process. By eliminating reliance on manual procedures and introducing robust consensus mechanisms, blockchain creates a more efficient and reliable certification process. This research contributes significantly to the understanding of how blockchain technology can be integrated into educational systems to enhance security and trust, and it opens avenues for further research on the long-term impact and potential adoption of blockchain in various educational certification contexts.